Isogenic Strain Construction and Gene Targeting in Candida dubliniensis - Staib, Peter (American Society for Microbiology, 2001)
Candida dubliniensis is a recently described opportunistic fungal pathogen that is closely related to Candida albicans but differs from it with respect to epidemiology, certain virulence characteristics, and the ability to develop fluconazole resistance in vitro. A comparison of C. albicans and C. dubliniensis at the molecular level should therefore provide clues about the mechanisms used by these two species to adapt to their human host. In contrast to C. albicans, no auxotrophic C. dubliniensis strains are available for genetic manipulations. Therefore, we constructed homozygous ura3 mutants from a C. dubliniensis wild-type isolate by targeted gene deletion. The two URA3 alleles were sequentially inactivated using the MPA(R)-flipping strategy, which is based on the selection of integrative transformants carrying a mycophenolic acid resistance marker that is subsequently deleted again by site-specific, FLP-mediated recombination. The URA3 gene from C. albicans (CaURA3) was then used as a selection marker for targeted integration of a fusion between the C. dubliniensis MDR1 (CdMDR1) promoter and a C. albicans-adapted GFP reporter gene. Uridine-prototrophic transformants were obtained with high frequency, and all transformants of two independent ura3-negative parent strains had correctly integrated the reporter gene fusion into the CdMDR1 locus, demonstrating that the CaURA3 gene can be used for efficient and specific targeting of recombinant DNA into the C. dubliniensis genome. Transformants carrying the reporter gene fusion did not exhibit detectable fluorescence during growth in yeast extract-peptone-dextrose medium in vitro, suggesting that CdMDR1 is not significantly expressed under these conditions. Fluconazole had no effect on MDR1 expression, but the addition of the drug benomyl strongly activated the reporter gene fusion in a dose-dependent fashion, demonstrating that the CdMDR1 gene, which encodes an efflux pump mediating resistance to toxic compounds, is induced by the presence of certain drugs.